Numerical simulation of the improved gas production from low permeability hydrate reservoirs by using an enlarged highly permeable well wall - Zhang, Jinming; Li, Xiaosen; Chen, Zhaoyang; Li, Qingping; Li, Gang; Lv, Tao (Journal of Petroleum Science and Engineering, 2019)
Gas production from low-permeability hydrate reservoirs is characterized by very low efficiency. In this work, the enlarged well wall with good permeability was first proposed to improve the gas production performance from low-permeability hydrate reservoir in Liwan 3 area of the South China Sea. The gas-water production behaviors, the spatial distributions and evolutions of hydrate reservoir parameters and gas-water flow characteristics, induced by constant-depressurization, were investigated and evaluated by numerical simulations under different radius of permeable well wall. Results show that the enlarged well wall provides a high-permeability channel around the production interval and increases the contact area between the production interval and hydrate layer, so the pressure drop propagation speed and distance, i.e. the depressurization efficiency in the hydrate-bearing sediments is increased. Both gas and water production performances are significantly improved, and the gas and water production rates, cumulates and gas to water ratio increase with the increase in permeable well wall radius. The cumulative CH4 and water produced increase by ca. 4 and 3 times, respectively, when the permeable well wall radius increases from 0 to 5 m. However, the heat supply by heat convection of geothermal water is still limited.